Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To complete the table of values for the function [tex]\( y = x^2 + x \)[/tex], we will evaluate the expression for each given value of [tex]\( x \)[/tex] and fill in the corresponding [tex]\( y \)[/tex] values.
Let's go through each calculation:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = (-2)^2 + (-2) = 4 - 2 = 2 \][/tex]
So, when [tex]\( x = -2 \)[/tex], [tex]\( y = 2 \)[/tex].
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = (-1)^2 + (-1) = 1 - 1 = 0 \][/tex]
So, when [tex]\( x = -1 \)[/tex], [tex]\( y = 0 \)[/tex]. This means [tex]\( A = 0 \)[/tex].
3. For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 0^2 + 0 = 0 + 0 = 0 \][/tex]
So, when [tex]\( x = 0 \)[/tex], [tex]\( y = 0 \)[/tex]. This means [tex]\( B = 0 \)[/tex].
4. For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 1^2 + 1 = 1 + 1 = 2 \][/tex]
So, when [tex]\( x = 1 \)[/tex], [tex]\( y = 2 \)[/tex].
5. For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2^2 + 2 = 4 + 2 = 6 \][/tex]
So, when [tex]\( x = 2 \)[/tex], [tex]\( y = 6 \)[/tex]. This means [tex]\( C = 6 \)[/tex].
Now, we can fill in the table:
[tex]\[ \begin{tabular}{c||c|c|c|c|c} $x$ & -2 & -1 & 0 & 1 & 2 \\ \hline $y$ & 2 & 0 & 0 & 2 & 6 \\ \end{tabular} \][/tex]
Therefore, the numbers that replace [tex]\( A \)[/tex], [tex]\( B \)[/tex] and [tex]\( C \)[/tex] are:
[tex]\[ A = 0, \quad B = 0, \quad C = 6. \][/tex]
Let's go through each calculation:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = (-2)^2 + (-2) = 4 - 2 = 2 \][/tex]
So, when [tex]\( x = -2 \)[/tex], [tex]\( y = 2 \)[/tex].
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = (-1)^2 + (-1) = 1 - 1 = 0 \][/tex]
So, when [tex]\( x = -1 \)[/tex], [tex]\( y = 0 \)[/tex]. This means [tex]\( A = 0 \)[/tex].
3. For [tex]\( x = 0 \)[/tex]:
[tex]\[ y = 0^2 + 0 = 0 + 0 = 0 \][/tex]
So, when [tex]\( x = 0 \)[/tex], [tex]\( y = 0 \)[/tex]. This means [tex]\( B = 0 \)[/tex].
4. For [tex]\( x = 1 \)[/tex]:
[tex]\[ y = 1^2 + 1 = 1 + 1 = 2 \][/tex]
So, when [tex]\( x = 1 \)[/tex], [tex]\( y = 2 \)[/tex].
5. For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2^2 + 2 = 4 + 2 = 6 \][/tex]
So, when [tex]\( x = 2 \)[/tex], [tex]\( y = 6 \)[/tex]. This means [tex]\( C = 6 \)[/tex].
Now, we can fill in the table:
[tex]\[ \begin{tabular}{c||c|c|c|c|c} $x$ & -2 & -1 & 0 & 1 & 2 \\ \hline $y$ & 2 & 0 & 0 & 2 & 6 \\ \end{tabular} \][/tex]
Therefore, the numbers that replace [tex]\( A \)[/tex], [tex]\( B \)[/tex] and [tex]\( C \)[/tex] are:
[tex]\[ A = 0, \quad B = 0, \quad C = 6. \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.